Controlling deposition of nanoparticles by tuning surface charge of SiO2 by surface modifications. Issue 106 (1st November 2016) - Eklöf, Johnas; Gschneidtner, Tina; Lara-Avila, Samuel; Nygård, Kim; Moth-Poulsen, Kasper
Abstract : The self-assembly of nanoparticles on substrates is relevant for a variety of applications such as plasmonics, sensing devices and nanometer-sized electronics. Abstract : The self-assembly of nanoparticles on substrates is relevant for a variety of applications such as plasmonics, sensing devices and nanometer-sized electronics. We investigate the deposition of 60 nm spherical Au nanoparticles onto silicon dioxide (SiO2 ) substrates by changing the chemical treatment of the substrate and by that altering the surface charge. The deposition is characterized by scanning electron microscopy (SEM). Kelvin probe force microscopy (KPFM) was used to characterize the surface workfunction. The underlying physics involved in the deposition of nanoparticles was described by a model based on Derjaguin–Landau–Verwey–Overbeek (DLVO) theory combined with random sequential adsorption (RSA). The spatial statistical method Ripley's K -function was used to verify the DLVO–RSA model (ERSA). The statistical results also showed that the adhered particles exhibit a short-range order at distances below ~300 nm. This method can be used in future research to predict the deposition densities of charged nanoparticles onto charged surfaces.